2011
DOI: 10.1038/ni.2107
|View full text |Cite
|
Sign up to set email alerts
|

The carboxypeptidase ACE shapes the MHC class I peptide repertoire

Abstract: The surface presentation of peptides by major histocompatibility complex (MHC) class I molecules is critical to CD8+ T cell mediated adaptive immune responses. Aminopeptidases are implicated in the editing of peptides for MHC class I loading, but C-terminal editing is thought due to proteasome cleavage. By comparing genetically deficient, wild-type and over-expressing mice, we now identify the dipeptidase angiotensin-converting enzyme (ACE) as playing a physiologic role in peptide processing for MHC class I. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 42 publications
3
76
0
2
Order By: Relevance
“…Using these mouse models, we demonstrated that ACE can also affect immune function (24)(25)(26). Specifically, ACE 10/10 mice had an increased immune response and decreased disease after challenge with tumors (24) or bacterial infections (25).…”
Section: Introductionmentioning
confidence: 99%
“…Using these mouse models, we demonstrated that ACE can also affect immune function (24)(25)(26). Specifically, ACE 10/10 mice had an increased immune response and decreased disease after challenge with tumors (24) or bacterial infections (25).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, the ACE 10/10 mice were generated by a promoter-swapping technique, where ACE expression was directed by the myelomonocytic lineagespecific c-fms promoter (65). Accordingly, these animals express nearly 20-fold increased ACE levels in macrophage and myeloid lineage cells (125,126). When these mice were challenged with several cancer cell lines including the B16-F10 melanoma and EL-4 lymphoma, they significantly resisted tumor growth compared with the wild-type (WT) counterparts (126).…”
Section: Ace and Myeloid Lineage Cellsmentioning
confidence: 99%
“…Human monocytes express minimal ACE, which is further upregulated as these cells differentiate into dendritic cells (38). We used Ly6C expression to sort monocytes in mouse and also observed a surge in ACE expression during differentiation into macrophages and dendritic cells (125). However, Balyasnikova et al (12) have previously demonstrated reduced ACE expression during differentiation of mouse monocytes into macrophages, based on CD 11b, F4/80 and Gr-1 expression.…”
Section: Ace and Myeloid Lineage Cellsmentioning
confidence: 99%
See 2 more Smart Citations